Psammomatous melanotic schwannoma presenting as colonic polyps. - Chetty, R; Vajpeyi, R; Penwick, J (2007)
Psammomatous melanotic schwannoma is an uncommon neoplasm that usually occurs in the setting of Carney's complex. They can occur in the gastrointestinal tract with preferential location in the stomach. A 43-year-old female presented with two colonic polyps at routine endoscopy. The patient was asymptomatic and did not have features of Carney's complex. Both polyps were composed of melanin-containing epithelioid and spindle cells with several psammoma bodies. There was no evidence of cytological atypia or necrosis. The tumor was diffusely positive for S-100, and focally for HMB-45 and melan-A. The differential diagnosis includes melanoma, GIST, pigmented neuroendocrine tumor, and epithelioid leiomyoma. The lack of malignant features separates this lesion from melanoma while the immunophenotype of the other lesions is characteristic.